Italian families in the 21st century: Gender gaps in time use and their evolution - Francesca Barigozzi; Cesare Di Timoteo; Chiara Monfardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
We provide novel estimates of gender differences in the allocation of time by Italian adults and document their trends over the span 2002-2014, pooling three time-use surveys run by the Italian National Institute of Statistics (ISTAT). The positive gap (females-males) in time devoted to Household work and the negative gap in Market work and Leisure are found to have narrowed over the observed period, mainly due to changes in women's time allocation, while the positive gap in time devoted to Child care remained substantially constant. In 2014, the sharing of family duties appears still heavily unbalanced even when we look at the subsample of full-time working parents. Full-time working mothers devote to Market work about 4 hours per week less than their partners, but they devote 14 hours per week more to Household work and 3 hours and a half more to Basic child care. This translates in 13 hours per week more total (paid and unpaid) work and 11 hours per week less Leisure. On the positive side, the gender gap in time devoted to Quality child care exhibits a reversed sign in 2014. The change is driven by weekend days, when partners of full-time working mothers become the main provider of this type of care.
Keywords: J13; J22; H31; 330; time use; gender gaps; child care; household work